Exosomal circEPB41L2 serves as a sponge for miR‐21‐5p and miR‐942‐5p to suppress colorectal cancer progression by regulating the PTEN/AKT signalling pathway. (22nd May 2021) - Jiang, Zhipeng; Hou, Zehui; Li, Liang; Liu, Wei; Yu, Zhuomin; Chen, Shuang
Abstract: Background: Exosomes contain many functional RNAs, including circular RNA (circRNA), which are critical for cancer progression. However, the role of exosomal circEPB41L2 in colorectal cancer (CRC) remains unclear. Methods: Exosomes were isolated from plasma and cells. The characteristics of the exosomes were identified using transmission electron microscopy and nanoparticle tracking analysis. The protein levels of exosome markers and PTEN/AKT‐related markers were measured using Western blot analysis. The expression of circEPB41L2, microRNA (miR)‐21‐5p and miR‐942‐5p was verified by quantitative real‐time PCR. The proliferation, apoptosis, migration and invasion of cells were determined using cell counting kit eight assay, colony formation assay, flow cytometry, wound healing assay and transwell assay. Biotin‐labelled RNA pull‐down assay, dual‐luciferase reporter assay and RIP assay were conducted to evaluate the interaction between circEPB41L2 and miR‐21‐5p or miR‐942‐5p. The effects of exosomal circEPB41L2 on colorectal cancer tumour growth were confirmed using animal experiments. Results: CircEPB41L2 was downregulated in the exosomes from colorectal cancer patients and cells. Overexpressed circEPB41L2 inhibited colorectal cancer cell proliferation, migration, invasion and promoted apoptosis, as well as suppressed the activity of PTEN/AKT signalling pathway. CircEPB41L2 could sponge miR‐21‐5p or miR‐942‐5p. MiR‐21‐5p or miR‐942‐5p could reverse the inhibition effect of circEPB41L2 on colorectal cancer progression and PTEN/AKT signalling pathway. In addition, we discovered that circEPB41L2 was mainly located at exosomes. Exosomal circEPB41L2 also could restrain colorectal cancer progression and the activity of PTEN/AKT signalling pathway. Animal experiments suggested that exosomal‐mediated circEPB41L2 inhibited colorectal cancer tumour growth. Conclusion: Our data revealed that exosomal circEPB41L2 sponged miR‐21‐5p and miR‐942‐5p to repress colorectal cancer progression by regulating the PTEN/AKT signalling pathway.